Fully-automated production of [68Ga]Ga-Trivehexin for clinical application and its biodistribution in healthy volunteers - Wang, Binchen; Jiang, Yaqun; Zhu, Jiaxu; Wu, Huiqin; Wu, Jianyuan; Li, Ling; Huang, Jianying; Xiao, Zhiwei; He, Yong (Frontiers in Oncology, 2024)
Background The αvβ6-integrin targeting trimeric ligand [68Ga]Ga-Trivehexin has emerged as a promising candidate for clinical application due to its clinical imaging potentials in various malignant cancers. Our objective was to develop a simplified and reproducible module-based automated synthesis protocol to expand its availability in clinical application. Methods The pH value and the precursor load of radiolabeling were explored using an iQS-TS fully-automated module. Radiochemical purity was evaluated by radio-HPLC and radio-TLC. The ethanol content, radionuclide purity and identity, bacterial endotoxins, sterility, and stability of the final product [68Ga]Ga-Trivehexin were all tested. Biodistribution of [68Ga]Ga-Trivehexin in healthy volunteers was also conducted. Results The synthesis was explored and established using fully-automated module with outstanding radiochemical purity (>99%). Considering molar activity and economic costs, a pH of 3.6 and precursor dose of 30 μg were determined to be optimal. All relevant quality control parameters were tested and met the requirement of European Pharmacopoeia. In vitro stability test and imaging in healthy volunteer indicated the practical significance in clinical routines. Conclusions A fully-automated synthesis protocol for [68Ga]Ga-Trivehexin using the iQS-TS synthesis module was achieved and conformed to the clinical quality standards. Clinical trial registration ClinicalTrials.gov, NCT05835570. Registered 28 April 2023, https://www.clinicaltrials.gov/study/NCT05835570.